METODE TERAPI ISLAM DALAM MERAWAT PASIEN GANGGUAN KEJIWAAN DI RUMAH SAKIT IBNU SINA MAKASSAR - Ardhiah Sulistiawaty; Sattu Alang; Syamsidar Syamsidar (Jurnal Dakwah Tabligh, 2019)
Psychic health is sometimes a problem that is often overlooked in human life. Though psychological health or mental health is as important as physical health. Psychic health in Islam includes the notion of Al-Mutmainnah, which is a peaceful heart, also Al-Sakinah, which is clean. Islam views mental health not only as a harmonious human interaction in worldly interests but also in the context of perfect faith integrity. To treat mental patients need counselling and psychotherapy. There are five things given by the Koran, namely in the form of guidance, wisdom, healing, light, and spirit. Counselling therapy and Quran therapy is a process of assistance to facilitate individuals to overcome their problems on a spiritual journey to God and need to tawadduk humble themselves by hoping for God's forgiveness and mercy.